Menstrual function and mental health of medical students during the COVID-19 pandemic: a continuous cross-sectional study - Tatiana I. Gorbacheva; Maria G. Nikolaeva; Alexander E. Stroganov; Olga V. Orlova; Larisa A. Khoreva; Yulia M. Uvarova; Ekaterina A. Denisyuk; Yury S. Olovyannikov (IP Berlin A.V., 2023)
Aim. To assess the impact of new coronavirus infection (NCI) and COVID-19 vaccination on menstrual function in comparison with the frequency of depressive disorders during the COVID-19 pandemic among female students of a medical university. Materials and methods. Data for a continuous transverse (cross-sectional) study were obtained using an online survey. The questions included demographics, characteristics of menstrual function, the history of COVID-19 and vaccinations against it, and the standard CES-D (Center for Epidemiologic Studies Depression Scale) questionnaire. The survey included 1.879 female medical students. The exclusion criteria were age under 18 and over 25 years, hormonal contraceptives, pregnancy, childbirth during the last year, and vaccination after COVID-19. After applying the exclusion criteria, three study groups were formed. Group 1 included female students with a history of NCI (n=140), group 2 included students with no history of NCI, who were initially vaccinated against COVID-19 (n=647), group 3 (control group) included unvaccinated students with no history of NCI (n=55). Results. There were no differences in the prevalence of changes in menstrual function in female students after the NCI (49.3%) and after COVID-19 vaccination (39.6%) compared to the control group (43.6%); p=0.477. The rate of depression in the overall study cohort was 43.3%, without any significant differences between the study groups. Significant predictors of changes in menstrual function during the pandemic were marriage (odds ratio OR 2.33 [1.513.61]), depression (OR 1.72 [1.282.3]), a history of menstrual dysfunction (OR 1.5 [0.121.99]), and later menarche (OR 1.76 [1.023.04]). Multivariate analysis did not show the significance of the history of NCI and vaccination as factors of menstrual dysfunction (OR 1.61 [0.892.90] and OR 0.91 [0.591.41], respectively). Conclusion. During the COVID-19 pandemic, female medical students reported frequent changes in menstrual function and depressive disorders. During the pandemic, the most significant predictors of menstrual disorders in female students were depression, a history of menstrual dysfunction, and marriage. A multicenter prospective study is necessary to clarify the mechanisms of the pandemic's impact on menstrual function.